Post-surgery rehabilitation following rotator cuff repair. A survey of current (2020) Italian clinical practice. Issue 17 (14th August 2022) - Brindisino, Fabrizio; De Santis, Andrea; Rossettini, Giacomo; Pellicciari, Leonardo; Filipponi, Marco; Rollo, Giuseppe; Gibson, Jo
Abstract: Aims: To analyse the clinical practice of Italian physiotherapists within the framework of postoperative rehabilitation of rotator cuff (RC) surgery patients, and to compare it with similar studies carried out in other countries. Methods: A web-based, voluntary, cross-sectional survey with 27 closed multiple-choice questions was developed and submitted to Italian-based physiotherapists in order to assess their clinical practice. Results: Data from 1160 questionnaires were then analysed. Thirty-five percent of respondents ( n = 413/1160) reported that they commence passive range of motion from the first postoperative week, while 49.2% ( n = 571/1160) start during the second or third week. The majority of respondents ( n = 603/1160, 52.0%) introduce active mobilisation between the fourth and the sixth week after surgery and 41.1% ( n = 477/1160) introduce overhead movements between the fourth and the sixth week after surgery. Discussion and conclusions: When managing the postoperative rehabilitation of RC surgery patients, Italian physiotherapists' practice is congruent with the guidelines published by American Society of Shoulder and Elbow Therapists (ASSET) and also with other UK surveys. However, while Italian physiotherapists manage immobilisation periods, active and passive mobilisation and the return to sport activities, according to evidence-based best practice guidelines, there is less consistency with respect to physical exercise, patient follow-up and referral. IMPLICATIONS FOR REHABILITATION: Italian physiotherapists' practice with patients following rotator cuff (RC) repair complies with evidence-based practice guidelines regarding immobilisation periods, passive and active mobilisation, and return to sport activities. There is less consistency between reported/declared practice and available evidence concerning physical exercise, patient follow-up, and referral. Physiotherapist with Orthopaedic Manipulative Physical Therapy (OMPT) training is more aligned with the current literature compared to physiotherapists without specific training, in terms of managing rehabilitation programmes, period of immobilisation and therapeutic exercise. More careful adherence to the international guidelines is recommended, in order to manage patients following RC repair in accordance with the evidence and to achieve the best possible outcomes.